The burden of attention deficit hyperactivity disorder and incidence rate forecast in China from 1990 to 2021 - Ningyu Li; Ningyu Li; Junqiang Zhao; Junqiang Zhao; Junqiang Zhao; Junqiang Zhao; Fujun Zhou (Frontiers in Psychiatry)
ObjectiveTo analyze the temporal trends and future projections of attention-deficit/hyperactivity disorder (ADHD) burden among children and adolescents in China from 1990 to 2021, and to identify age-, period-, and cohort-specific drivers of disease progression.MethodsUsing data from the Global Burden of Disease Study 2021, we conducted joinpoint regression to detect trend transitions in ADHD incidence and age-standardized rates. Age-period-cohort (APC) modeling was applied to disentangle the effects of age, calendar period, and birth cohort on disease burden. Projections up to 2046 were generated using demographic forecasts from the GBD 2017 population database.ResultsCrude ADHD prevalence declined by 21.17% (2168.055 to 1723.307 per 100,000), yet age-standardized prevalence increased by 9.86% (AAPC=0.272%, 95%CI:0.173–0.372, P<0.001). Similarly, age-standardized DALY rates rose by 10.15% (AAPC=0.262%, 95%CI:0.160–0.364,P<0.001), with females showing faster growth than males (AAPC for DALY: 0.294% vs. 0.229%,P<0.001). Adolescents aged 10–14 years bore the highest burden, with prevalence (5,727.28/100,000) and DALY rates (70.55/100,000) twice the global average. APC projections indicated a peak incidence in 2029 for this age group, linked to cohort effects from China’s “Double Reduction” education policy and rising digital exposure.ConclusionChina faces a rising ADHD burden driven by sociodemographic transitions and diagnostic advancements. Targeted interventions—particularly for adolescents and females—are urgently needed. Strengthening school-based screening, integrating AI-driven diagnostic tools, and prioritizing mental health in national policies could mitigate long-term impacts. These findings underscore the necessity of dynamic surveillance systems to address ADHD’s evolving epidemiology in transitioning societies.